2019
DOI: 10.1016/j.jstrokecerebrovasdis.2019.104348
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Auricular Vagus Nerve Stimulation with Upper Limb Repetitive Task Practice May Improve Sensory Recovery in Chronic Stroke

Abstract: Background-Sensory impairment is associated with reduced functional recovery in stroke survivors. Invasive vagus nerve stimulation (VNS) paired with rehabilitative interventions improves motor recovery in chronic stroke. Non-invasive approaches e.g. transcutaneous auricular VNS (taVNS) are safe, well-tolerated and may also improve motor function in those with residual weakness. We report the impact of taVNS paired with a motor intervention, repetitive task practice, on sensory recovery in a cohort of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 15 publications
1
42
0
1
Order By: Relevance
“…We know direct electrical efferent and afferent VNS. Moreover, several transcutaneous VNS (Baig et al 2019 ) approaches are also in use (Johnston and Webster 2009 ). Recently, Staats et al (Staats et al 2020 ) reported distinct symptom relief (fatigue, low appetite, and coughing bouts such as dyspnea and chest pressure/tightness) in two SARS-CoV-2 positive tested patients under the usage of noninvasive vagal nerve stimulation (nVNS).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…We know direct electrical efferent and afferent VNS. Moreover, several transcutaneous VNS (Baig et al 2019 ) approaches are also in use (Johnston and Webster 2009 ). Recently, Staats et al (Staats et al 2020 ) reported distinct symptom relief (fatigue, low appetite, and coughing bouts such as dyspnea and chest pressure/tightness) in two SARS-CoV-2 positive tested patients under the usage of noninvasive vagal nerve stimulation (nVNS).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Recent clinical trials show that VNS can improve upper extremity motor function in stroke patients with upper extremity motor dysfunction [ 6 , 7 ]. Transcutaneous auricular vagus nerve stimulation (taVNS) is a noninvasive method of VNS via transcutaneous stimulation of the peripheral auricular branch of the vagus nerve [ 8 ] and regarded as a potentially safer, better-tolerated method for sensory and motor recovery in chronic stroke [ 9 , 10 ]. Previously, one study has reported that taVNS improves neurobehavioral recovery in acute stroke rats [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kilgard and colleagues found that invasive VNS stimulation delivered at 30 Hz was associated with improved somatosensory function in a patient with severe sensory impairment due to stroke [14]. Similarly, a study of twelve stroke patients that received auricular VNS at 25 Hz during performance of a motor task found that most patients showed post-intervention increases in sensory function [8].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty (20) subjects were randomly assigned to each of four stimulation frequency groups (30Hz, 300Hz, 3kHz, or sham). Thirty (30) Hz stimulation was chosen because frequencies in this range are associated with high degrees of cortical plasticity changes in animal experiments [13] and have been used in previous studies of stroke patients [8,14]. Higher frequencies were included based on their use in other cranial nerve studies [9,15] and observations that these frequencies Figure 2.…”
Section: B Stimulation Protocolmentioning
confidence: 99%
See 1 more Smart Citation